Electric welded steel pipe and method for manufacturing same
By controlling the particle size and shape of the central austenite of steel pipes, inhibiting the formation of coarse grains, and combining with appropriate tempering treatment, the problem of difficult to take into account both the high strength and high machining properties of steel pipes in the prior art is achieved, and high toughness and Manufacturing of electric welded steel pipes with excellent processability.
Patent Information
- Application Number
- CN202280094366.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-27
- Filing Date
- 2022-11-08
- Publication Date
- 2025-01-07
AI Technical Summary
The prior art is difficult to maintain high toughness while improving the high strength and processability of steel pipes, especially in low temperature environments, and there is a risk of breakage in the bending processing method, which fails to effectively suppress the decline in toughness and processability caused by coarse grains.
By controlling the average particle size and shape of the original austenite, it is uniform and fine, inhibiting the formation of thick martensite, and combining appropriate tempering conditions and movable dislocation density, martensite welded steel pipes are prepared to improve their strength and processability, and ensure uniform grain distribution through specific hot rolling and quenching processes.
It has achieved high strength, excellent machining and high toughness of steel pipes, meeting the component needs of automobiles, construction machinery and industrial machinery, and significantly improved performance in low temperature environments.
Smart Images

Figure CN119278285A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an electric welded steel pipe and a method for manufacturing the same. Background Art
[0002] In recent years, in order to improve fuel consumption and miniaturize equipment, automobiles, construction machinery, and industrial machinery have been pursuing high strength of components. In addition, the steel pipes used for mechanical structures are required to have high processability in order to be bent, hydraulically expanded, and expanded according to the application. In addition, the above-mentioned automobiles, construction machinery, and industrial machinery are sometimes used in cold regions, so high low-temperature toughness is also required.
[0003] However, when the strength of a part is increased, workability and toughness are reduced, and there is a problem that the part cannot be used for the intended purpose.
[0004] In order to solve the above problems, for example, Japanese Patent Application Publication No. 2019-112705 (Patent Document 1) proposes a seamless steel pipe having a structure in which the size of prior austenite grains is greater than 9.0 in terms of grain size number, a tensile strength of greater than 700 MPa, and an elongation of greater than 25%.
[0005] In addition, International Publication No. 2020 / 075297 (Patent Document 2) proposes an electric-welded steel pipe for a torsion beam characterized by a small aspect ratio of prior austenite grains of tempered martensite, a tensile strength of 750 to 980 MPa in the tube axis direction, and high bending formability.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2019-112705
[0009] Patent Document 2: International Publication No. 2020 / 075297 Summary of the invention
[0010] However, the steel pipes described in Patent Documents 1 and 2 ensure high toughness and high workability by controlling the average grain size and shape of prior austenite, but it is difficult to suppress the reduction in toughness and workability due to the presence of local coarse grains by these methods alone.
[0011] In addition, as a processing method for pipes, bending is often performed. In this case, the processability can be improved by suppressing fracture on the outer side of the bend and suppressing buckling on the inner side of the bend, but Patent Documents 1 and 2 do not study this from such a viewpoint, and further improvement is required.
[0012] The present disclosure has been made in view of the above circumstances, and an object of the present disclosure is to provide a high-strength, excellent workability and toughness electric resistance welded steel pipe suitable for a machine structure steel pipe used in parts of automobiles, construction machinery, and industrial machinery, and a method for producing the same.
[0013] It should be noted that the term "high strength" as used herein means that the yield stress in the tube axis direction is 650 MPa or more and the tensile strength is 750 MPa or more. Preferably, the yield stress is 700 MPa or more and the tensile strength is 800 MPa or more.
[0014] The term "high processability" or "excellent processability" as used herein means that the yield ratio in the tube axis direction (= (yield stress / tensile strength) × 100) is 93% or less and the total elongation in the tube axis direction is 20% or more, and the load P (N) at the time of crack generation in the flattening test (JIS G3441) satisfies the following formula (1). It should be noted that the yield ratio in the tube axis direction is preferably 90% or less. In addition, the total elongation in the tube axis direction is preferably 25% or more.
[0015] P ≥ 1.5 × TS × t 2 ×L / D···(1)
[0016] In formula (1), TS is the tensile strength (MPa), D is the outer diameter (mm), t is the wall thickness of the steel pipe (mm), and L is the length in the pipe axial direction (mm).
[0017] The term "high toughness" or "excellent toughness" as used herein means that the Charpy impact value at -60°C is 60 J / cm 2 Above. Preferably 70 J / cm 2 above.
[0018] The present inventors have conducted intensive studies on the above-mentioned problems and have found that if part of prior austenite is coarse, martensite generated therefrom is also coarse, thereby reducing toughness and workability.
[0019] If the structure is coarse, the proportion of high-angle grain boundaries, which are barriers to brittle fracture, decreases, so the toughness decreases. In addition, even if the average grain size is small, if there is a certain proportion of coarse grains, they become the starting point of brittle fracture, so the toughness still decreases.
[0020] That is, the present inventors have considered that by making prior austenite uniform and fine and suppressing the formation of coarse martensite, uniform and fine martensite can be obtained, thereby improving toughness and workability.
[0021] In addition, it was found that uniform and fine martensite can achieve both high strength and low yield ratio by properly controlling tempering conditions and movable dislocation density. It was also found that uniform and fine martensite increases uniform elongation, reduces deviation in wall thickness distribution during deformation, and further improves workability.
[0022] The present disclosure has been completed through further research based on such findings. That is, the gist of the present disclosure is as follows.
[0023] 1. An electric-resistance welded steel pipe comprising a base material portion and a weld portion, wherein the composition comprises, by mass%, C: 0.150% to 0.500%, Si: 0.05% to 1.00%, Mn: 0.10% to 2.00%, P: 0.050% or less, S: 0.0200% or less, Al: 0.005% to 0.100%, N: 0.0100% or less, Cr: 0.10% to 1.00%, and B: 0.0002% to 0.0050%, with the remainder being Fe and inevitable impurities, the steel structure at the center of the wall thickness of the base material portion being martensite with a volume fraction of 90% or more, and the remainder comprising one or more of ferrite, bainite, pearlite and austenite, the average crystal grain size being 10 μm or less, and the volume fraction of prior austenite with a grain size of 50 μm or more being 40% or less.
[0024] 2. The electric resistance welded steel pipe according to item 1 above, further comprising, in addition to the above-mentioned component composition, one or more selected from the group consisting of Cu: 1.00% or less, Ni: 1.00% or less, Mo: 1.00% or less, Nb: 0.150% or less, V: 0.150% or less, Ti: 0.150% or less, and Ca: 0.0100% or less, in terms of mass %.
[0025] 3. The electric resistance welded steel pipe according to item 1 above is a method for producing an electric resistance welded steel pipe according to item 1 or 2 above, wherein the component composition is, in mass %, P: 0.002% to 0.050%, S: 0.0002% to 0.0200%, and N: 0.0010% to 0.0100%.
[0026] 4. A method for manufacturing an electric-welded steel pipe, which is the method for manufacturing an electric-welded steel pipe as described in any one of 1 to 3 above, comprising the following steps:
[0027] The hot rolling process is to heat the steel billet to a heating temperature of 1100°C to 1300°C, and then perform hot rolling at a rough rolling end temperature of 850°C to 1150°C, a finish rolling end temperature of 750°C to 900°C, and a total reduction ratio of 50% or more at a temperature of 930°C or less.
[0028] A cooling process, after the hot rolling process, is performed at an average cooling rate of 5°C / s to 30°C / s at the center of the plate thickness and a cooling stop temperature of 400°C to 650°C at the center of the plate thickness;
[0029] A coiling process, after the cooling process, coiling at 400°C to 650°C to produce a hot-rolled steel sheet;
[0030] The pipe making process is to form the hot-rolled steel sheet into a cylindrical shape by cold roll forming, and then to carry out electric resistance welding to form a steel pipe blank;
[0031] A shaping step of reducing the circumference of the steel tube billet by a ratio of 3.0% or less;
[0032] A quenching step, after the shaping step, heating at a temperature range of 850°C to 1050°C for 100s to 1000s, followed by cooling to below 100°C at an average cooling rate of 40°C / s from at least the center of the wall thickness between 800°C and 400°C, based on the center temperature of the wall thickness;
[0033] The tempering step is performed after the quenching step by heating at a temperature range of 450° C. to 600° C. for a period of more than 70 seconds.
[0034] 5. The method for producing an electric resistance welded steel pipe according to 4 above, wherein the heating time in the temperature range of 450° C. to 600° C. in the tempering step is set to 100 s to 1000 s.
[0035] According to the present disclosure, it is possible to provide an electric resistance welded steel pipe having high strength and excellent workability and toughness, which is suitable for a steel pipe for machine structure used in parts of automobiles, construction machinery, and industrial machinery, and a method for producing the same. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a schematic diagram of a cross section in the pipe circumferential direction (a cross section perpendicular to the pipe axis direction) of the electric resistance welded portion of an electric-welded steel pipe. DETAILED DESCRIPTION
[0037] Figure 1The vertical cross section in the pipe axis direction of the electric resistance welded steel pipe according to the present disclosure is shown. The electric resistance welded steel pipe according to the present disclosure includes a base material portion 1 and a weld portion (a weld heat affected zone 2 and a joint portion 3 to be described later). The base material portion 1 of the electric-resistance welded steel pipe disclosed herein contains, by mass%, C: 0.150% to 0.500%, Si: 0.05% to 1.00%, Mn: 0.10% to 2.00%, P: 0.050% or less, S: 0.0200% or less, Al: 0.005% to 0.100%, N: 0.0100% or less, Cr: 0.10% to 1.00%, B: 0.0002% to 0.0050%, and the remainder is Fe and inevitable impurities. The steel structure at the center of the wall thickness of the base material portion 1 is such that the volume fraction of martensite is 90% or more, and the remainder contains one or more of ferrite, bainite, pearlite and austenite, the average crystal grain size is 10 μm or less, and the volume fraction of prior austenite having a grain size of 50 μm or more is 40% or less.
[0038] Hereinafter, the electric resistance welded steel pipe and the method for producing the same according to the present disclosure will be described.
[0039] First, in the present disclosure, the component composition of the base material portion 1 of the electric resistance welded steel pipe will be described. In the present specification, "%" indicating the component composition means "mass %" unless otherwise specified.
[0040] (C: 0.150%~0.500%)
[0041] C is an element that improves the strength of steel by solid solution strengthening. In addition, C is an element that improves hardenability and contributes to the formation of martensite. In order to obtain such an effect, 0.150% or more of C is contained. On the other hand, if the C content exceeds 0.500%, the strength becomes too high and the workability and toughness decrease, and the weldability also deteriorates. Therefore, the C content is set to 0.150% to 0.500%. The C content is preferably 0.180% or more, and more preferably 0.200% or more. On the other hand, the C content is preferably 0.480% or less, and more preferably 0.460% or less.
[0042] (Si: 0.05% to 1.00%)
[0043] Si is an element that improves the strength of steel by solid solution strengthening. In addition, Si is an element that improves hardenability and contributes to the formation of martensite. In order to obtain such an effect, 0.05% or more of Si is contained. On the other hand, if the Si content exceeds 1.00%, the strength becomes too high and the workability and toughness decrease. In addition, oxides are easily generated in the resistance welding part, and the characteristics of the welding part decrease. Therefore, the Si content is set to 0.05% to 1.00%. The Si content is preferably 0.08% or more, and more preferably 0.10% or more. On the other hand, the Si content is preferably 0.80% or less, and more preferably 0.50% or less.
[0044] (Mn: 0.10% to 2.00%)
[0045] Mn is an element that improves the strength of steel by solid solution strengthening. In addition, Mn is an element that improves hardenability and contributes to the formation of martensite. In order to obtain such an effect, it is necessary to contain more than 0.10% Mn. On the other hand, if the Mn content exceeds 2.00%, the strength becomes too high and the workability and toughness decrease. In addition, oxides are easily generated in the resistance welding part, and the characteristics of the welding part decrease. Therefore, the Mn content is set to 0.10% to 2.00%. The Mn content is preferably more than 0.20%, and more preferably more than 0.30%. On the other hand, the Mn content is preferably less than 1.50%, and more preferably less than 1.20%.
[0046] (P: 0.050% or less)
[0047] P segregates at grain boundaries and causes unevenness in the material, so as an inevitable impurity, it is preferably reduced as much as possible, but a maximum of 0.050% is allowed. Therefore, in the present disclosure, the P content is set to 0.050% or less. The P content is preferably 0.020% or less, and more preferably 0.010% or less. It should be noted that there is no particular lower limit for P, but excessive reduction will lead to an increase in refining costs, so the P content is preferably 0.002% or more.
[0048] (S: 0.0200% or less)
[0049] S usually exists in steel as MnS, but MnS is stretched and thinned during the hot rolling process, which has an adverse effect on ductility and toughness. Therefore, in the present disclosure, as an unavoidable impurity, it is preferred to reduce S as much as possible, but a maximum of 0.0200% is allowed. Therefore, the S content is set to 0.0200% or less. The S content is preferably 0.0100% or less, and more preferably 0.0080% or less. It should be noted that the lower limit of S is not particularly specified, but excessive reduction leads to a rise in refining costs, so S is preferably 0.0002% or more.
[0050] (Al: 0.005% to 0.100%)
[0051] Al is an element that acts as a strong deoxidizer. In order to obtain such an effect, it is necessary to contain 0.005% or more of Al. On the other hand, if the Al content exceeds 0.100%, the weldability deteriorates, the number of alumina inclusions increases, and the surface properties deteriorate. In addition, the toughness of the weld also decreases. Therefore, the Al content is set to 0.100% or less. The Al content is preferably 0.010% or more, and more preferably 0.015% or more. On the other hand, the Al content is preferably 0.080% or less, and more preferably 0.070% or less.
[0052] (N: 0.0100% or less)
[0053] N is an inevitable impurity and an element that has the effect of firmly fixing the movement of dislocations to reduce ductility and toughness. In the base material part 1 of the present disclosure, N as an impurity is preferably reduced as much as possible, but the maximum allowable N content is 0.0100%. Therefore, the N content is set to 0.0100% or less. The N content is preferably 0.0080% or less. It should be noted that there is no lower limit for N, but excessive reduction leads to a rise in refining costs, so N is preferably 0.0010% or more.
[0054] (Cr: 0.10%~1.00%)
[0055] Cr is an element that improves hardenability and contributes to the formation of martensite and increases the strength of steel. In order to obtain such an effect, it is necessary to contain 0.10% or more of Cr. On the other hand, if the Cr content exceeds 1.00%, the strength becomes too high and the workability and toughness decrease. In addition, oxides are easily generated in the resistance welding part, and the characteristics of the welding part decrease. Therefore, the Cr content is set to 0.10% to 1.00%. The Cr content is preferably 0.15% or more, and more preferably 0.20% or more. On the other hand, the Cr content is preferably 0.80% or less, and more preferably 0.60% or less.
[0056] (B: 0.0002%~0.0050%)
[0057] B is an element that improves hardenability and contributes to the formation of martensite and improves the strength of steel. In order to obtain such an effect, it is necessary to contain 0.0002% or more of B. On the other hand, if the B content exceeds 0.0050%, the strength becomes too high and the workability and toughness decrease. Therefore, the B content is set to 0.0002% to 0.0050%. The B content is preferably 0.0003% or more, more preferably 0.0005% or more. On the other hand, the B content is preferably 0.0040% or less, more preferably 0.0030% or less.
[0058] The remainder is Fe and inevitable impurities. Among them, as an inevitable impurity, 0.0050% or less of O may be contained. It should be noted that O in the present disclosure refers to the total oxygen including O as an oxide.
[0059] The above-mentioned components are the basic component composition of the electric-resistance welded steel pipe of the present disclosure.
[0060] Furthermore, one or more selected from the group consisting of Cu: 1.00% or less, Ni: 1.00% or less, Mo: 1.00% or less, Nb: 0.150% or less, V: 0.150% or less, Ti: 0.150% or less, and Ca: 0.0100% or less may be contained as necessary.
[0061] (Cu: 1.00% or less)
[0062] Cu is an element that improves the strength of steel by solid solution strengthening, and can be contained as needed. In order to obtain the above-mentioned effect, when Cu is contained, the Cu content is preferably 0.01% or more. On the other hand, containing more than 1.00% Cu may lead to a decrease in toughness and deterioration of weldability. Therefore, when Cu is contained, the Cu content is preferably 1.00% or less. The Cu content is more preferably 0.05% or more, and further preferably 0.10% or more. On the other hand, the Cu content is more preferably 0.70% or less, and further preferably 0.50% or less.
[0063] (Ni: 1.00% or less)
[0064] Ni is an element that improves the strength of steel by solid solution strengthening, and can be contained as needed. In order to obtain the above-mentioned effect, when Ni is contained, the Ni content is preferably 0.01% or more. On the other hand, containing more than 1.00% Ni may lead to a decrease in toughness and workability and deterioration of weldability. Therefore, when Ni is contained, the Ni content is preferably 1.00% or less. The Ni content is more preferably 0.05% or more, and further preferably 0.10% or more. On the other hand, the Ni content is more preferably 0.70% or less, and further preferably 0.50% or less.
[0065] (Mo: 1.00% or less)
[0066] Mo is an element that improves the hardenability of steel and the strength of steel, and can be contained as needed. In order to obtain the above-mentioned effect, when Mo is contained, the Mo content is preferably 0.01% or more. On the other hand, containing more than 1.00% of Mo may lead to a decrease in toughness and workability and a deterioration in weldability. Therefore, when Mo is contained, the Mo content is preferably 1.00% or less. The Mo content is more preferably 0.05% or more, and further preferably 0.10% or more. On the other hand, the Mo content is more preferably 0.70% or less, and further preferably 0.50% or less.
[0067] (Nb: 0.150% or less)
[0068] Nb is an element that contributes to the improvement of the strength of steel by forming fine carbides and nitrides in steel. In addition, it is an element that contributes to the refinement of the structure by suppressing the coarsening of austenite during hot rolling. It can be contained as needed. In order to obtain the above-mentioned effect, when Nb is contained, it is preferred to contain 0.002% or more of Nb. On the other hand, if the Nb content exceeds 0.150%, the toughness and workability decrease. Therefore, when Nb is contained, the Nb content is preferably 0.150% or less. The Nb content is more preferably 0.005% or more, and further preferably 0.010% or more. On the other hand, the Nb content is more preferably 0.100% or less, and further preferably 0.080% or less.
[0069] (V: 0.150% or less)
[0070] V is an element that contributes to improving the strength of steel by forming fine carbides and nitrides in steel, and can be contained as needed. In order to obtain the above-mentioned effect, when V is contained, it is preferred to contain 0.002% or more of V. On the other hand, if the V content exceeds 0.150%, the toughness and workability decrease. Therefore, when V is contained, the V content is preferably 0.150% or less. The V content is more preferably 0.005% or more, and further preferably 0.010% or more. On the other hand, the V content is more preferably 0.100% or less, and further preferably 0.080% or less.
[0071] (Ti: 0.150% or less)
[0072] Ti is an element that contributes to improving the strength of steel by forming fine carbides and nitrides in steel, and contributes to refining the structure by suppressing the coarsening of austenite during hot rolling, and can be contained as needed. In addition, due to its high affinity with N, it makes N in steel harmless as nitrides, and is an element that contributes to improving the toughness of steel. In order to obtain the above-mentioned effect, when containing Ti, it is preferably contained at least 0.002% Ti. On the other hand, if the Ti content exceeds 0.150%, the yield ratio becomes higher and the toughness decreases. Therefore, the Ti content is preferably less than 0.150%. The Ti content is more preferably more than 0.005%, and further preferably more than 0.008%. On the other hand, the Ti content is more preferably less than 0.130%, and further preferably less than 0.110%.
[0073] (Ca: 0.0100% or less)
[0074] Ca is an element that helps improve the toughness of steel by spheroidizing sulfides such as MnS that are stretched and thinned in the hot rolling process, and can be contained as needed. In order to obtain the above-mentioned effect, when Ca is contained, it is preferred to contain 0.0005% or more of Ca. On the other hand, if the Ca content exceeds 0.0100%, Ca oxide clusters are formed in the steel, and the toughness deteriorates. Therefore, when Ca is contained, the Ca content is preferably 0.0100% or less. The Ca content is more preferably 0.0008% or more, and further preferably 0.0010% or more. On the other hand, the Ca content is more preferably 0.0080% or less, and further preferably 0.0060% or less.
[0075] Next, the steel structure of the electric resistance welded steel pipe of the present disclosure will be described.
[0076] In the steel structure in the center of the wall thickness of the base material portion 1 in the electric-resistance welded steel pipe disclosed herein, it is required that the volume fraction of martensite is 90% or more, the remainder contains one or more of ferrite, bainite, pearlite and austenite, the average crystal grain size is 10 μm or less, and the volume fraction of prior austenite with a grain size of 50 μm or more is 40% or less.
[0077] (Volume ratio of martensite: 90% or more)
[0078] Martensite is a hard structure. In order to obtain the strength required in the present disclosure, 90% or more of martensite is required by volume. The volume fraction of martensite is preferably 93% or more, and more preferably 95% or more. On the other hand, from the viewpoint of processability, the volume fraction of martensite is preferably 99% or less, and more preferably 98% or less.
[0079] [The rest: one or more of ferrite, bainite, pearlite and austenite]
[0080] The remaining part of the center of the wall thickness of the base material part 1 of the electric welded steel pipe is set to one or more of ferrite, bainite, pearlite and austenite. These structures have different strengths from martensite, and by mixing with martensite, the yield ratio can be reduced and the total elongation can be increased. On the other hand, at the interface between these structures and martensite, fracture is easily caused due to stress concentration caused by strength difference, so when these structures become more, the toughness decreases. Therefore, the combined volume ratio of these structures is less than 10% relative to the overall structure in the same field of view at this position, preferably less than 7%, and more preferably less than 5%. It should be noted that it is difficult to completely suppress these structures in the quenching process, and in order to ensure processability, about 1% is allowed as the lower limit.
[0081] In the electric welded steel pipe disclosed in the present invention, it is sufficient that at least the above-mentioned steel structure exists within a range of ±0.20 mm in the wall thickness direction, centered on the center of the wall thickness of the base material portion 1 (the position of 1 / 2 of the wall thickness). If such a steel structure exists, a steel structure within the range of the present invention can also be obtained at other positions in the wall thickness direction of the base material portion 1, so the effect of the present invention can be obtained in the same manner. This is because the cooling rate in the quenching process is lowest at the center of the wall thickness. Therefore, in the present disclosure, the "steel structure at the center of the wall thickness" refers to a specified area (preferably 0.10 mm2) existing at any point within a range of ±0.20 mm in the wall thickness direction, centered on the center of the wall thickness. 2 Steel structure of the above).
[0082] The observation of the steel structure is carried out as follows. First, a test piece for structure observation is taken in a manner that the observation surface is a vertical cross-section in the long side direction of the tube of the base material part 1 and the center of the wall thickness, and after grinding, it is made by nitric acid etching. Next, the structure observation uses an optical microscope (magnification: 1000 times) and / or a scanning electron microscope (SEM, magnification: 1000 times) to observe the structure of the above-mentioned test piece and photograph it. The area ratio of martensite and the remaining part (ferrite, pearlite, bainite, austenite) is calculated from the optical microscope image and / or SEM image obtained in this way. The area ratio of each structure is observed in more than 5 fields of view and calculated as the average value of the values obtained in each field of view. It should be noted that in the present disclosure, the area ratio obtained by the above-mentioned structure observation is used as the volume ratio of each structure.
[0083] Here, ferrite is a product obtained by diffusion phase transformation, and has a low dislocation density and a nearly recovered structure, including polygonal ferrite and quasi-polygonal ferrite.
[0084] Bainite is a multiphase structure of lath-shaped ferrite and cementite with high dislocation density.
[0085] Pearlite is a eutectic structure of iron and iron carbide (ferrite + cementite), showing a layered structure with linear ferrite and cementite arranged alternately.
[0086] Martensite is a lath-shaped low-temperature phase transformation structure with extremely high dislocation density. In SEM images, it shows a bright contrast compared to ferrite and bainite.
[0087] It should be noted that it is difficult to distinguish martensite and austenite in the above optical microscope image and SEM image. Therefore, the area ratio of the structure observed as martensite or austenite is calculated from the obtained SEM image, and the value obtained by subtracting the volume ratio of austenite measured by the following method from the area ratio is used as the volume ratio of martensite.
[0088] Here, the volume fraction of austenite is measured by X-ray diffraction using a test piece prepared in the same manner as the above test piece, and is obtained from the integrated intensity of the (200), (220), and (311) planes of fcc iron and the (200) and (211) planes of bcc iron obtained by the X-ray diffraction.
[0089] (Average crystal particle size: 10 μm or less)
[0090] When the average crystal grain size of the grains of the steel structure in the center of the wall thickness of the parent material part 1 exceeds 10 μm, the total area of the grain boundaries that hinder crack propagation is small, so the desired toughness cannot be obtained. Therefore, in the parent material part 1 disclosed in the present invention, the average crystal grain size of the above-mentioned grains is set to be less than 10 μm. The average crystal grain size of the above-mentioned grains is preferably less than 8.0 μm, and more preferably less than 6.0 μm. It should be noted that when the average crystal grain size is too small, the processability decreases, so the average crystal grain size is preferably 3.0 μm or more.
[0091] In the present disclosure, the average crystal grain size refers to the average equivalent circle diameter of the crystal grain when the region surrounded by the boundary where the orientation difference of adjacent crystals is 15° or more is the crystal grain. In addition, the equivalent circle diameter (crystal grain size) refers to the diameter of a circle equal to the area of the crystal grain as the object.
[0092] As the measurement of the average crystal grain size, first, the cross section parallel to both the tube length direction and the wall thickness direction of the base material part 1 is mirror-polished, and the histogram of the particle size distribution is calculated using the SEM / EBSD method in the center of the wall thickness (set as the horizontal axis: particle size, the vertical axis: the existence ratio of each particle size), and the arithmetic mean of the particle size is obtained as the average crystal grain size. As the measurement conditions, the acceleration voltage is 15kV, the measurement area is 500μm×500μm, and the measurement step length (measurement resolution) is 0.5μm. It should be noted that in the crystal grain size analysis, the results with a crystal grain size less than 2.0μm are excluded from the analysis object as measurement noise. The average crystal grain size is measured in more than 5 times and is calculated as the average value of the values obtained in each field of view.
[0093] (Grain size: 50 μm or more, the volume fraction of prior austenite is 40% or less)
[0094] If the volume fraction of the original austenite with a grain size of 50 μm or more (hereinafter also referred to as "coarse original austenite") in the original austenite in the steel structure at the center of the wall thickness of the parent material portion 1 exceeds 40%, and the proportion of coarse grains becomes high, cracks are likely to propagate through the coarse grains, so the desired toughness cannot be obtained. In addition, during processing, strain is concentrated on the coarse grains, and fracture occurs early, so the desired processability cannot be obtained. Therefore, in the parent material portion 1 disclosed in the present invention, the volume fraction of coarse original austenite is set to 40% or less. The volume fraction of coarse original austenite is preferably 35% or less, and more preferably 30% or less.
[0095] It should be noted that the volume ratio of coarse prior austenite is measured as follows. First, a cross section parallel to both the tube length direction and the wall thickness direction of the base material portion 1 is ground, and then corroded with a saturated picric acid aqueous solution to expose the prior austenite grain boundary. An optical microscope (magnification: 400 times) is used to photograph the structure in the center of the wall thickness in 5 or more fields of view, and a histogram of the prior austenite grain size distribution is calculated in each field of view. The area ratio of the equivalent circle diameter of 50 μm or more is obtained and is taken as the volume ratio of the prior austenite with a grain size of 50 μm or more.
[0096] Alternatively, instead of the etching with the saturated picric acid aqueous solution, the SEM / EBSD method may be used to delineate the boundaries with orientation differences of 20° to 50° as prior austenite grain boundaries, and use the boundaries to calculate a histogram of prior austenite grain size distribution.
[0097] The histogram of the prior austenite grain size distribution can be obtained by calculating the area of each prior austenite grain using image processing software (eg, ImageJ1.52p).
[0098] It should be noted that the electric resistance welded steel pipe of the present disclosure is composed of a base material portion 1 and a weld portion, and the component composition and steel structure of the weld portion of the electric resistance welded steel pipe are the same as those of the base material portion 1 .
[0099] Next, a method for producing an electric resistance welded steel pipe according to an embodiment of the present disclosure will be described.
[0100] The method for manufacturing an electric-welded steel pipe disclosed in the present invention, for example, includes the following steps: a hot rolling step, in which a steel billet having the above-mentioned component composition is heated to a heating temperature of 1100° C. to 1300° C., and then hot-rolled at a rough rolling end temperature of 850° C. to 1150° C., a finish rolling end temperature of 750° C. to 900° C., and a total reduction ratio of 50% or more at 930° C. or less to produce a hot-rolled plate; a cooling step, in which, after the hot rolling step, the hot-rolled plate is cooled at an average cooling rate of 5° C. / s to 30° C. / s at a cooling stop temperature of 400° C. to 650° C.; a coiling step, in which, after the cooling step, the hot-rolled plate is coiled at 400° C. to 650° C. to produce a hot-rolled steel plate; and a pipe making step, in which the hot-rolled plate is rolled at a temperature of 400° C. to 650° C. to produce a hot-rolled steel plate. The hot rolled steel sheet is formed into a cylindrical shape by cold rolling, and then subjected to electric resistance welding to form a steel pipe billet; a shaping step, after the pipe making step, the steel pipe billet is reduced in diameter in a manner that the circumference is reduced by a ratio of 3.0% or less; a quenching step, after the shaping step, the steel pipe billet is heated at a temperature of 850°C to 1050°C for a time of 100s to 1000s, and then the average cooling rate of the wall thickness center from at least 800°C to 400°C is set to 40°C / s or more, and then cooled to 100°C or less, based on the wall thickness center temperature; a tempering step, after the quenching step, the steel pipe billet is heated at a temperature range of 450°C to 600°C for a time of more than 70s.
[0101] It should be noted that the above-mentioned hot-rolled steel sheet also includes a hot-rolled plate and a hot-rolled steel strip.
[0102] In the following description of the manufacturing method, unless otherwise specified, the temperature-related "°C" expression refers to the surface temperature of the steel billet, steel plate (hot-rolled plate), steel pipe billet and steel pipe. These surface temperatures can be measured using a radiation thermometer or the like, and the temperature of the center of the steel plate thickness, the center of the steel pipe wall thickness, etc. is calculated by heat transfer analysis to calculate the temperature distribution in the cross section of the steel plate, steel pipe, etc., and the result is corrected according to the surface temperature of the steel plate, steel pipe, etc.
[0103] In the present disclosure, the smelting method of the steel billet (steel billet) is not particularly limited, and known smelting methods such as converters, electric furnaces, and vacuum melting furnaces are all suitable. The casting method is also not particularly limited, but the desired size can be produced by known casting methods such as continuous casting. It should be noted that there is no problem in applying the ingot casting-opening rolling method instead of the continuous casting method. The molten steel can also be further subjected to secondary refining such as ladle refining.
[0104] [Hot rolling process]
[0105] (Heating temperature: 1100℃~1300℃)
[0106] When the heating temperature is less than 1100°C, the deformation resistance of the rolled material becomes large, and rolling becomes difficult. On the other hand, if the heating temperature exceeds 1300°C, the austenite grains coarsen, and in the subsequent rolling (rough rolling, finish rolling), fine austenite grains cannot be obtained, and the structure of the hot-rolled steel sheet coarsens. As a result, the nucleation sites of austenite during heating in the quenching process are reduced, and the austenite (original austenite of the electric-welded steel pipe) generated in the quenching process coarsens, and the average crystal grain size of the steel structure of the electric-welded steel pipe and the volume ratio of the coarse original austenite as the target in the present disclosure cannot be obtained. The heating temperature is more preferably above 1120°C. On the other hand, the heating temperature is more preferably below 1280°C.
[0107] It should be noted that in the manufacturing method disclosed herein, in addition to the conventional method of temporarily cooling the steel billet (slab) to room temperature and then reheating it after manufacturing, the energy-saving direct rolling processes of loading the steel billet into a heating furnace in a warm sheet state without cooling to room temperature or immediately rolling the steel billet after a slight heat preservation can also be applied without any problems.
[0108] (Rough rolling end temperature: 850℃~1150℃)
[0109] When the rough rolling end temperature is less than 850°C, the surface temperature of the steel plate reaches below the ferrite transformation start temperature in the subsequent finish rolling, and coarse ferrite is generated, which causes excessive generation of coarse prior austenite in the subsequent quenching process. As a result, the average crystal grain size of the steel structure of the electric-resistance welded steel pipe and the volume ratio of coarse prior austenite, which are the targets of the present disclosure, cannot be obtained. On the other hand, if the rough rolling end temperature exceeds 1150°C, the reduction amount in the austenite non-recrystallization temperature range is insufficient, the austenite of the steel billet is coarsened, and the structure of the hot-rolled steel plate is coarsened, which causes the generation of coarse prior austenite in the subsequent quenching process. As a result, the average crystal grain size of the steel structure of the electric-resistance welded steel pipe and the volume ratio of coarse prior austenite, which are the targets of the present disclosure, cannot be obtained. The rough rolling end temperature is more preferably 880°C or more. On the other hand, the rough rolling end temperature is more preferably 1100°C or less.
[0110] The start temperature of the finishing rolling in the present disclosure is preferably in the range of 800°C to 950°C. When the start temperature of the finishing rolling is less than 800°C, the surface temperature of the steel plate during the finishing rolling reaches below the ferrite transformation start temperature, and coarse ferrite is generated, which becomes the cause of the generation of coarse prior austenite in the subsequent quenching process. As a result, the average crystal grain size of the steel structure of the electric resistance welded steel pipe as the target in the present disclosure and the volume ratio of coarse prior austenite may not be obtained. On the other hand, if the start temperature of the finishing rolling exceeds 950°C, the reduction amount in the austenite non-recrystallization temperature range is insufficient, thereby coarsening the austenite of the steel billet and the structure of the hot-rolled steel plate, which becomes the cause of the generation of coarse prior austenite in the subsequent quenching process. As a result, the average crystal grain size of the steel structure of the electric resistance welded steel pipe as the target in the present disclosure and the volume ratio of coarse prior austenite may not be obtained. It should be noted that the start temperature of the finishing rolling is more preferably 820°C or more. On the other hand, the start temperature of the finishing rolling is more preferably 930°C or less.
[0111] (Finish rolling end temperature: 750℃~900℃)
[0112] When the finishing temperature of the finishing rolling is less than 750°C, the surface temperature of the steel plate reaches below the ferrite transformation start temperature during the finishing rolling, and coarse ferrite is generated, which becomes the cause of the generation of coarse prior austenite in the subsequent quenching process. As a result, the average crystal grain size of the steel structure of the electric-welded steel pipe as the target in the present disclosure and the volume ratio of coarse prior austenite cannot be obtained. On the other hand, if the finishing temperature of the finishing rolling exceeds 900°C, the reduction amount in the austenite non-recrystallization temperature range is insufficient, thereby coarsening the austenite of the steel billet and the structure of the hot-rolled steel plate, which becomes the cause of the generation of coarse prior austenite in the subsequent quenching process. As a result, the average crystal grain size of the steel structure of the electric-welded steel pipe as the target in the present disclosure and the volume ratio of coarse prior austenite cannot be obtained. The finishing temperature of the finishing rolling is more preferably 770°C or more. On the other hand, the finishing temperature of the finishing rolling is more preferably 880°C or less.
[0113] (Total reduction ratio below 930°C: 50% or more)
[0114] In the manufacturing method disclosed herein, the microstructure of the hot-rolled steel sheet is refined by refining the subgrains in the austenite in the hot rolling process, thereby obtaining the microstructure of the electric-resistance welded steel pipe having the target average crystal grain size and the volume ratio of the coarse prior austenite. In addition, during the heating in the quenching process, austenite is mainly generated from the grain boundaries with large orientation differences. Thus, by refining the microstructure before the quenching process, the area of the grain boundaries as the nucleation sites of the austenite increases, and the austenite generated in the quenching process can be refined.
[0115] In the hot rolling process, in order to refine the subgrains in austenite, it is necessary to increase the reduction ratio in the austenite non-recrystallization temperature range and introduce sufficient processing strain. To achieve this condition, in the manufacturing method disclosed herein, the total reduction ratio of the hot rolling process at 930°C or less is set to 50% or more.
[0116] The above-mentioned total rolling reduction ratio refers to the total rolling reduction ratios of the respective rolling passes in the temperature range of 930° C. or lower.
[0117] If the total reduction ratio is less than 50%, sufficient processing strain cannot be introduced in the hot rolling process, so the structure of the electric resistance welded steel pipe having the average crystal grain size and the volume ratio of coarse prior austenite targeted in the present disclosure cannot be obtained. The total reduction ratio is preferably 55% or more.
[0118] It should be noted that there is no particular upper limit to the total reduction rate, but if it exceeds 80%, the effect of improving toughness and workability relative to the increase in the reduction rate becomes smaller, and it only leads to an increase in equipment load. Therefore, the above-mentioned total reduction rate is preferably 80% or less. More preferably, it is 70% or less.
[0119] 〔Cooling process〕
[0120] In the manufacturing method disclosed herein, a cooling treatment is performed on the hot-rolled sheet in a cooling process after the hot-rolling process. In the cooling process, the average cooling rate of the center of the thickness of the hot-rolled sheet until the cooling stop temperature is reached is set to 5°C / s to 30°C / s, and the cooling stop temperature of the center of the thickness of the hot-rolled sheet is set to 400°C to 650°C.
[0121] (Average cooling rate from the start of cooling to the end of cooling (cooling end): 5℃ / s~30℃ / s)
[0122] At the center of the plate thickness of the hot-rolled plate, if the average cooling rate in the temperature range from the start of cooling to the stop of cooling described later is less than 5°C / s, the nucleation frequency decreases, the structure of the hot-rolled steel plate coarsens, and thus the structure of the electric-welded steel pipe having the average crystal grain size and the volume ratio of coarse prior austenite as the target in the present disclosure cannot be obtained. On the other hand, if the average cooling rate exceeds 30°C / s, a large amount of martensite is generated, and the ductility and toughness decrease. Therefore, forming in the subsequent pipe making process becomes difficult.
[0123] The average cooling rate is preferably 10° C. / s or more. On the other hand, the average cooling rate is preferably 25° C. / s or less.
[0124] In addition, in the manufacturing method of the present disclosure, in order to suppress the formation of ferrite on the surface of the hot-rolled sheet before cooling, it is preferable to start cooling immediately after the finish rolling is completed.
[0125] (Cooling stop temperature: 400℃~650℃)
[0126] When the cooling stop temperature is less than 400°C at the center of the hot-rolled plate thickness, a large amount of martensite is generated, and the ductility and toughness decrease, so that forming in the subsequent pipe making process becomes difficult. On the other hand, if the cooling stop temperature exceeds 650°C, the nucleation frequency decreases, and the structure of the hot-rolled steel plate coarsens, so the structure of the electric-welded steel pipe having the average crystal grain size and the volume ratio of coarse prior austenite as the target in the present disclosure cannot be obtained. The cooling stop temperature is preferably 430°C or more. On the other hand, the cooling stop temperature is preferably 620°C or less.
[0127] In addition, in this disclosure, the average cooling rate refers to the value (cooling rate) calculated from ((the plate thickness center temperature of the hot-rolled plate before cooling-the plate thickness center temperature of the hot-rolled plate after cooling) / cooling time).
[0128] In addition, the cooling method includes water cooling by spraying water from a nozzle, cooling by spraying a cooling gas, etc. In the manufacturing method disclosed herein, it is preferred that both surfaces of the hot-rolled sheet be cooled under the same conditions by cooling operation (treatment).
[0129] 〔Winding process〕
[0130] After the above-mentioned cooling process, the hot-rolled sheet is coiled into a coil in the coiling process and then cooled. When the coiling temperature is less than 400°C, a large amount of martensite is generated, and the ductility and toughness decrease, so that the forming in the subsequent pipe making process becomes difficult. On the other hand, if the coiling temperature exceeds 650°C, the nucleation frequency decreases, and the structure of the hot-rolled steel sheet coarsens, so the structure of the electric welded steel pipe having the average crystal grain size and the volume ratio of coarse prior austenite as the target in the present disclosure cannot be obtained. The coiling temperature is preferably above 430°C. On the other hand, the coiling temperature is preferably below 620°C. It should be noted that in the present disclosure, the steel sheet in which the hot-rolled sheet is coiled into a coil is referred to as a hot-rolled steel sheet.
[0131] 〔Pipe making process〕
[0132] After the coiling process, the hot-rolled steel sheet is subjected to a tube-making process. In this tube-making process, the hot-rolled steel sheet is continuously led out and formed into a cylindrical open tube (round steel tube) by cold rolling, and the circumferential butt joint of the open tube is melted by high-frequency resistance heating, and resistance welding is performed by pressure-joining by upsetting with an extrusion roll to produce a steel tube billet.
[0133] The upset amount during the above-mentioned resistance welding (hereinafter referred to as the upset amount) is preferably set to 20% or more of the plate thickness so that inclusions such as oxides and nitrides that cause a decrease in toughness can be discharged together with the molten steel. However, if the upset amount exceeds 100% of the plate thickness, the squeeze roll load becomes too large. Therefore, the upset amount is preferably 20% to 100% of the plate thickness. The upset amount is more preferably 40% or more of the plate thickness. On the other hand, the upset amount is more preferably 80% or less of the plate thickness.
[0134] The upset amount is determined as the difference between the outer circumference of the steel pipe (open pipe) before electric resistance welding and the outer circumference of the steel pipe after electric resistance welding.
[0135] [Shaping process: reducing the diameter of the steel pipe billet so that the circumference is reduced by 3.0% or less]
[0136] In the shaping process after the pipe making process, the steel pipe material is reduced in diameter by rollers provided above, below, left and right of the steel pipe material, and the outer diameter and roundness are adjusted to desired values.
[0137] In the shaping process, if the diameter is reduced in a manner that the total circumference of the steel pipe is reduced by more than 3.0%, the deviation of the dislocation density of each grain becomes large, and in the subsequent quenching process, strain-induced grain boundary migration occurs, which becomes a cause of the formation of coarse prior austenite. Therefore, it is important to reduce the diameter in a manner that the circumference of the steel pipe is reduced by less than 3.0%. It is preferably less than 2.5%. On the other hand, in order to improve the accuracy and roundness of the outer diameter, it is preferred to reduce the diameter of the steel pipe billet in a manner that the total circumference of the steel pipe is reduced by more than 0.5%. It is more preferably more than 1.0%.
[0138] [Quenching process: heating the steel pipe billet at a temperature range of 850°C to 1050°C for a period of 100s to 1000s]
[0139] When the heating temperature in the quenching process is less than 850°C or the heating time is less than 100s, the structure is not completely austenitized, so the desired volume fraction of martensite cannot be obtained. On the other hand, when the heating temperature in the quenching process is greater than 1050°C or the heating time is greater than 1000s, the austenite is coarsened, and the average crystal grain size of the steel structure of the electric-resistance welded steel pipe and the volume fraction of coarse prior austenite that are the target of the present disclosure cannot be obtained. The heating temperature in the quenching process is preferably 880°C or more, preferably 1000°C or less. In addition, the heating time in the quenching process is preferably 200s or more, preferably 800s or less.
[0140] (Based on the wall thickness center temperature, the average cooling rate of the wall thickness center between 800°C and 400°C should be set to 40°C / s or more)
[0141] In the manufacturing method of the present disclosure, the temperature range for defining the average cooling rate in the quenching step is set to at least 800° C. to 400° C. Ferrite, pearlite, and bainite are generated within this temperature range.
[0142] In addition, when the average cooling rate of the wall thickness center of the steel tube billet in the quenching process is less than 40°C / s, the desired martensite fraction cannot be obtained. It is preferably 50°C / s or more. There is no upper limit for the average cooling rate, but if it exceeds 150°C / s, the effect of strength improvement relative to the increase in cooling rate becomes smaller, which only leads to an increase in equipment load. Therefore, the average cooling rate is preferably 150°C / s or less. More preferably, it is 130°C / s or less.
[0143] Here, if the wall thickness center temperature after cooling in the quenching process is higher than 100° C., the desired martensite fraction cannot be obtained. Therefore, it is important to reduce the wall thickness center temperature after cooling in the quenching process of the present disclosure to 100° C. or less. It should be noted that the wall thickness center temperature after cooling in the quenching process is preferably 60° C. or less.
[0144] [Tempering process: heating the steel pipe billet at a temperature range of 450℃~600℃ for more than 70s]
[0145] If the heating temperature in the tempering process is less than 450°C or the heating time is less than 70s, the desired toughness and workability cannot be obtained due to insufficient recovery of dislocations. Furthermore, due to insufficient recovery of movable dislocations, too many movable dislocations remain, so the stress relaxation amount increases, the yield stress decreases, and the desired yield stress cannot be obtained. On the other hand, when the heating temperature in the tempering process is greater than 600°C, due to excessive recovery of movable dislocations, the stress relaxation amount decreases excessively, the yield stress and yield ratio increase, and the workability decreases. The heating temperature in the tempering process is preferably greater than 480°C and preferably less than 570°C.
[0146] In addition, when the heating time in the tempering step exceeds 1000 s, the movable displacement is excessively recovered, the stress relaxation amount is excessively reduced, the yield stress and the yield ratio are increased, and the workability may be reduced.
[0147] Therefore, the heating time is preferably 1000 s or less, more preferably 800 s or less. On the other hand, the heating time is preferably 100 s or more, more preferably 200 s or more.
[0148] In addition, the cooling method after heating in the tempering step may be any of air cooling, water cooling, furnace cooling, etc., and the conditions are not particularly limited, and the cooling is performed to room temperature.
[0149] The electric resistance welded steel pipe of the present disclosure is manufactured through the above steps. It should be noted that the electric resistance welded steel pipe of the present disclosure has high strength and excellent workability and toughness.
[0150] Furthermore, in the electric resistance welded steel pipe of the present disclosure, it is preferred that the stress relaxation amount at a stress of 40% of the yield stress is 0.50% to 5.00% of the yield stress.
[0151] The above-mentioned stress relaxation amount is a value relative to the mobile dislocation density. The larger the value, the more mobile dislocations there are, and plastic deformation is possible under low stress, so the yield stress decreases, the yield ratio decreases, and the workability becomes higher.
[0152] When the stress relaxation amount at 40% of the yield stress is less than 0.50% of the yield stress, the mobile dislocation density is too low, the yield stress and the yield ratio become high, and the desired workability may not be obtained. On the other hand, when the stress relaxation amount at 40% of the yield stress is greater than 5.00% of the yield stress, the mobile dislocation density becomes too high, and the desired yield stress may not be obtained.
[0153] In addition, the load P (N) at the time of crack generation in the flattening test of the electric resistance welded steel pipe of the present disclosure satisfies the formula (1).
[0154] P ≥ 1.5 × TS × t 2 ×L / D···(1)
[0155] In formula (1), TS is the tensile strength (MPa), D is the outer diameter (mm), t is the wall thickness (mm), and L is the length in the tube axis direction (mm).
[0156] When a tube is bent, the cross section of the tube changes from a perfect circle to an ellipse, causing buckling on the inside of the bend or breaking on the outside of the bend. If the ellipse deformation of the cross section of the tube is large, buckling on the inside of the bend will occur early. On the other hand, if the yield ratio is high and the elongation is small, breaking on the outside of the bend will occur early.
[0157] In addition, the larger the load P when cracks are generated in the flattening test, the greater the resistance to the elliptical deformation of the pipe circumferential cross section, and the elliptical deformation is less likely to occur. As a result, buckling of the inner side of the bend is less likely to occur, and the welded steel pipe has excellent workability.
[0158] According to preliminary experiments using conventional materials, it was found that the load P at which cracks are generated in the flattening test is proportional to TS, inversely proportional to D, proportional to the square of t, and proportional to L.
[0159] Therefore, an electric resistance welded steel pipe satisfying the formula (1) means an electric resistance welded steel pipe having better workability than conventional materials.
[0160] For the electric-resistance welded steel pipe disclosed herein, when a cross section perpendicular to the pipe axis direction and including the weld (resistance weld) is ground, corroded with a corrosive liquid, and observed under an optical microscope, the width of the joint 3 of the weld (resistance weld) in the pipe circumferential direction is 1.0 μm to 1000 μm over the entire thickness of the pipe.
[0161] Here, the etching liquid can be appropriately selected according to the steel composition and the type of steel pipe. Figure 1 As shown schematically, the above cross section after corrosion can be used as Figure 1 It is identified as an area having a different organizational morphology and contrast from the base material part 1 and the heat-affected part 2. For example, the joint 3 of the electric-welded steel pipe of carbon steel and low-alloy steel can be determined as a white area observed under an optical microscope in the above cross section after being corroded with nital. In addition, the joint 3 of the UOE steel pipe of carbon steel and low-alloy steel can be confirmed as an area containing a cellular or dendritic solidification structure under an optical microscope in the above cross section after being corroded with nital. It should be noted that in the present disclosure, the weld refers to the above-mentioned joint 3 and the heat-affected part 2.
[0162] The wall thickness of the electric resistance welded steel pipe disclosed in the present invention is preferably 1.5 mm to 20 mm. In addition, the outer diameter of the electric resistance welded steel pipe disclosed in the present invention is preferably 20 mm to 250 mm.
[0163] The conditions for the method of manufacturing the steel pipe not described above may be based on conventional methods.
[0164] Example
[0165] Hereinafter, the present disclosure will be further described based on examples. It should be noted that the present disclosure is not limited to the following examples.
[0166] Molten steel having the component composition shown in Table 1 was melted to produce slabs. The obtained slabs were subjected to the hot rolling process, cooling process, and coiling process under the conditions shown in Table 2 to produce hot-rolled steel sheets. It should be noted that regarding the numbers of steel pipes, the same numbers in all tables refer to the same tests (examples).
[0167] After the coiling process, the hot-rolled steel sheet is formed into a cylindrical round steel pipe by roll forming, and the butt joint is subjected to electric resistance welding. Then, a shaping process of reducing the diameter according to the reduction ratio shown in Table 2 is performed by rollers arranged above, below, left and right of the round steel pipe, and then, after a quenching and tempering process under the conditions shown in Table 2, an electric-welded steel pipe having an outer diameter D (mm) and a wall thickness t (mm) shown in Table 2 is obtained.
[0168] Various test pieces were taken from the electric resistance welded steel pipe thus obtained, and the following microstructure analysis, tensile test, stress relaxation test, Charpy impact test and flattening test were performed. The test pieces for microstructure analysis, tensile test, stress relaxation test and Charpy impact test were taken from the base material portion which was 90° away from the electric resistance welded portion in the pipe circumferential direction. The flattening test piece was a ring-shaped test piece having a length L of 100 mm in the pipe axial direction.
[0169]
[0170]
[0171] 〔Organization Observation〕
[0172] A test piece for structure observation was prepared by taking a cross section parallel to both the tube longitudinal direction and the wall thickness direction and at the center of the wall thickness, mirror-polishing the test piece, and etching with nital.
[0173] The structural observation was carried out by observing the structure in the center of the wall thickness using an optical microscope (magnification: 1000 times) and a scanning electron microscope (SEM, magnification: 1000 times), and taking optical microscope images and SEM images. The area ratios of ferrite, bainite, pearlite and the remaining part (martensite, austenite) were calculated from the obtained optical microscope images and SEM images. The area ratio of each structure was observed in 5 fields of view and calculated as the average value of the values obtained in each field of view. Here, the area ratio obtained by structural analysis is used as the volume ratio of each structure.
[0174] It should be noted that since martensite and austenite are difficult to distinguish in optical microscope images and SEM images, the area ratio of the structure observed as martensite or austenite was measured from the obtained SEM image, and the value obtained by subtracting the volume ratio of austenite measured by the following method was used as the volume ratio of martensite.
[0175] That is, the volume fraction of austenite is measured by X-ray diffraction using a test piece prepared in the same manner as the test piece for dislocation analysis. The measurement uses Mo Kα rays, and the integrated intensities of the (200), (220), and (311) planes of fcc iron and the (200) and (211) planes of bcc iron are respectively obtained. The standardized integrated intensity obtained by dividing each value by the theoretical intensity value is proportional to the volume fraction of each phase, and the ratio of the standardized integrated intensity of austenite is obtained, thereby obtaining the volume fraction of austenite.
[0176] In the determination of average crystal grain size, first use SEM / EBSD method to calculate the histogram of particle size distribution (set as horizontal axis: particle size, vertical axis: figure of the existence ratio of each particle size), and find the arithmetic mean of particle size. Specifically, for crystal grain size, find the orientation difference between adjacent crystal grains, take the boundary with orientation difference of more than 15 ° as crystal grain (grain boundary), measure the equivalent circle diameter of crystal grain, and use the average equivalent circle diameter as average crystal grain size. At this time, equivalent circle diameter refers to the diameter of a circle equal to the crystal grain area as the object.
[0177] The measurement conditions are as follows: acceleration voltage of 15 kV, measurement area of 500 μm×500 μm, and measurement step length of 0.5 μm. It should be noted that in the crystal grain size analysis, the results of crystal grains with a diameter of 2.0 μm or less are excluded from the analysis object as measurement noise, and the obtained area ratio is equal to the volume ratio.
[0178] 〔Tensile test〕
[0179] The tensile test was conducted by taking a JIS 12A tensile test piece in a manner that the tensile direction was parallel to the longitudinal direction of the tube, and the test piece was subjected to the test in accordance with the provisions of JIS Z 2241. The yield stress YS (MPa), tensile strength TS (MPa), and total elongation EL (%) were measured, and the yield ratio YR (%) defined by (YS / TS)×100 was calculated.
[0180] 〔Stress relaxation test〕
[0181] The stress relaxation test was conducted by taking a JIS 12A tensile test piece in a manner that the tensile direction was parallel to the longitudinal direction of the tube, and the test was conducted in accordance with the provisions of JIS Z 2276. The initial stress was set to 40% of the yield stress obtained in the tensile test. The displacement retention time was 500 s, and the stress drop during this period was taken as the stress relaxation amount.
[0182] 〔Charpy impact test〕
[0183] The Charpy impact test was conducted at -60°C in accordance with JIS Z 2242, by taking a V-notch test piece from the center of the wall thickness of the base material portion of the obtained electric resistance welded steel pipe so that the long side direction of the test piece was parallel to the pipe axis direction, and the absorbed energy was determined.
[0184] The number of test pieces in the Charpy impact test was set to three each, and the average value of the obtained impact values was taken as the Charpy impact value of the base material portion of the hot-rolled steel sheet and the electric resistance welded steel pipe.
[0185] 〔Flattening test〕
[0186] The flattening test was conducted by taking a ring-shaped test piece having a length L of 100 mm in the pipe axial direction from the obtained electric resistance welded steel pipe, grinding it so that the outer pipe surface of the welded portion showed metallic luster, and conducting the test according to the method described in JIS G 3441. The compression speed was set to 10 mm / min, and the compression was stopped at the time when cracks occurred, and the load at that time was defined as the load P (N) when cracks occurred.
[0187] The results obtained by these tests are shown in Table 3.
[0188]
[0189] In Table 3, No. 1 to 5, 17, and 18 are examples of the present disclosure, and No. 6 to 16 and 19 are comparative examples.
[0190] In the steel structure at the center of the wall thickness of the base material portion of the electric resistance welded steel pipe of the Example, the volume fraction of martensite is 90% or more, the average crystal grain size is 10 μm or less, and the volume fraction of prior austenite with a grain size of 50 μm or more is 40% or less.
[0191] In addition, the mechanical properties of the electric welded steel pipes of these examples are that the yield stress is 650 MPa or more, the tensile strength is 780 MPa or more, the yield ratio is 93% or less, the total elongation is 20% or more, and the Charpy impact value at -60°C is 60 J / cm 2 As described above, the load P (N) at the time of crack generation in the flattening test satisfies the above formula (1).
[0192] In contrast, in the steel pipe No. 6 of the comparative example, since the C content was high, the yield ratio, total elongation, Charpy absorbed energy at -60°C, and the load P at the time of crack initiation in the flattening test did not reach the desired values.
[0193] In the steel pipe No. 7 of the comparative example, since the C content was low, the volume fraction of martensite was lower than the range of the present disclosure, and the yield stress and tensile strength did not reach the desired values.
[0194] Since the steel pipe No. 8 of the comparative example has high contents of Si and Mn, the yield ratio, total elongation, Charpy absorbed energy at -60°C and load P at the time of crack initiation in the flattening test did not reach the desired values.
[0195] In the steel pipe No. 9 of the comparative example, since the Si and Mn contents were low, the volume fraction of martensite was lower than the range of the present disclosure, and the yield stress and tensile strength did not reach the desired values.
[0196] Since the Cr content of the steel pipe No. 10 of the comparative example was high, the yield ratio, total elongation, Charpy absorbed energy at -60°C, and the load P at the time of crack initiation in the flattening test did not reach the desired values.
[0197] In the steel pipe No. 11 of the comparative example, the Cr content was low, and the volume fraction of martensite was lower than the range of the present disclosure, so that the yield stress and the tensile strength did not reach the desired values.
[0198] Since the steel pipe No. 12 of the comparative example had a high B content, the yield elongation, the Charpy absorbed energy at -60°C, and the load P at the time of crack initiation in the flattening test did not reach the desired values.
[0199] In the steel pipe No. 13 of the comparative example, the B content was low, and the volume fraction of martensite was lower than the range of the present disclosure, so the yield stress and the tensile strength did not reach the desired values.
[0200] In the steel pipe No. 14 of the comparative example, the average cooling rate in the cooling step was slow, the average crystal grain size was higher than the range of the present disclosure, and the total elongation and the Charpy absorption energy at -60°C did not reach the desired values.
[0201] In the steel pipe No. 15 of the comparative example, the total reduction ratio below 930°C in the hot rolling process was low, and the volume ratio of the prior austenite with a grain size of 50 μm or more was higher than the range disclosed in the present invention, so the yield ratio, total elongation, Charpy absorbed energy at -60°C and the load P at the time of crack initiation in the flattening test did not reach the desired values.
[0202] In the steel pipe No. 16 of the comparative example, the temperature in the tempering step was high, so the stress relaxation amount became small and the yield ratio did not reach the desired value.
[0203] In the steel pipe No. 19 of the comparative example, the time in the tempering step was short, so the amount of stress relaxation became large and the yield stress did not reach the desired value.
[0204] Explanation of symbols
[0205] 1. Parent material department
[0206] 2. Heat affected zone (welding zone)
[0207] 3Jointing part (welding part)
Claims
1. An electric welded steel pipe having a base metal portion and a welded portion. The composition contains, by mass%, C: 0.150% to 0.500%, Si: 0.05% to 1.00%, Mn: 0.10% to 2.00%, P: 0.050% or less, S: 0.0200% or less, Al: 0.005% to 0.100%, N: 0.0100% or less, Cr: 0.10% to 1.00% and B: 0.0002% to 0.0050%, and the remainder is composed of Fe and inevitable impurities. The steel structure at the center of the wall thickness of the base material portion is as follows: the volume fraction of martensite is greater than 90%, the remainder comprises one or more of ferrite, bainite, pearlite and austenite, the average crystal grain size is less than 10 μm, and the volume fraction of original austenite with a grain size of greater than 50 μm is less than 40%.
2. The electric-welded steel pipe according to claim 1, wherein: In addition to the above-mentioned component composition, it further contains, in terms of mass%, one or more selected from the group consisting of Cu: 1.00% or less, Ni: 1.00% or less, Mo: 1.00% or less, Nb: 0.150% or less, V: 0.150% or less, Ti: 0.150% or less, and Ca: 0.0100% or less.
3. The electric-welded steel pipe according to claim 1, wherein: The component composition is, by mass%, P: 0.002% to 0.050%, S: 0.0002% to 0.0200%, and N: 0.0010% to 0.0100%.
4. A method for manufacturing an electric-welded steel pipe, which is the method for manufacturing an electric-welded steel pipe according to any one of claims 1 to 3, comprising the following steps: The hot rolling process is to heat the steel billet to a heating temperature of 1100°C to 1300°C, and then perform hot rolling at a rough rolling end temperature of 850°C to 1150°C, a finish rolling end temperature of 750°C to 900°C, and a total reduction ratio of 50% or more at a temperature of 930°C or less; A cooling step, after the hot rolling step, is performed at an average cooling rate of 5°C / s to 30°C / s at the center of the plate thickness and a cooling stop temperature of 400°C to 650°C at the center of the plate thickness; A coiling process, after the cooling process, coiling at 400°C to 650°C to produce a hot-rolled steel sheet; A pipe making step of forming the hot-rolled steel sheet into a cylindrical shape by cold rolling and then performing electric resistance welding to form a steel pipe blank; A shaping step of reducing the circumference of the steel tube billet by a ratio of 3.0% or less; A quenching step, after the shaping step, heating at a temperature range of 850°C to 1050°C for 100s to 1000s, followed by cooling to below 100°C at an average cooling rate of 40°C / s from at least the center of the wall thickness between 800°C and 400°C, based on the center temperature of the wall thickness; The tempering step is performed after the quenching step by heating at a temperature range of 450° C. to 600° C. for a period of more than 70 seconds.
5. The method for manufacturing an electric-resistance welded steel pipe according to claim 4, wherein: The heating time in the temperature range of 450° C. to 600° C. in the tempering step is set to 100 s to 1000 s.
Citation Information
Patent Citations
Seamless steel tube and manufacturing method of seamless steel tube
JP2019112705A
Electric resistance welded steel pipe for torsion beam
WO2020075297A1